Menakar Urgensi Kriminalisasi Kepemilikan Harta Tidak Wajar melalui Kebijakan Legislasi dalam Upaya Pemberantasan Tindak Pidana Korupsi di Indonesia - Rieska Ayu Bella Pratiwi; Nur Khamnari Derby Pambudi (Jurnal Penelitian Hukum De Jure, 2024)
Ownership of inappropriate assets by public officials or named illicit enrichment is still a hot issue. Indonesia itself has a wealth reporting instrument for public officials called the State Officials' Wealth Report (LHKPN) as a means of controlling and supervising the wealth of public officials. In practice, many public officials have unappropriate assets and are suspected to have been obtained illegally, but these assets cannot be taken by the state because they have not been or have been proven to be the proceeds of criminal act. Thus, this research aims to examine the potential for resolving this problem by criminalizing the ownership of improper assets by public officials, which aims to minimize the incidence of state financial losses. Based on the results of the research, it shows that there are at least two alternative ways, namely (a) making the illegal ownership of public officials whose legality is not proven to be one of the criminal offenses of corruption through the revision of the Corruption Law; or (b) formulate and ratify provisions related to illicit enrichment in the Asset Confiscation Bill. The criminalization of illicit enrichment is a form of implementation of the provisions of Article 20 of the United Nations Convention Against Corruption (UNCAC) as ratified by Indonesia with Law Number 7 of 2006 with the aim of preventing corrupt actions by public officials. This research uses a normative research method with a regulatory-legislative approach and a conceptual approach, the results of which are presented in prescriptive form.